ملامح السلطة والمجتمع في الجزائر خلال العهد العثماني من خلال كتابات غربية - أوجرنتي محمد (University of Eloued جامعة الوادي, 2023)
الملخص: إن البحث في تاريخ الجزائر خلال العهد العثماني له أهمية بالغة نظرا لارتباطه بتاريخ الجزائر خلال فترة الاحتلال وتكون شخصية الجزائر الحديثة التي حاول المؤرخون الفرنسيون طمسها وتذويبها ضمن فلسفة التاريخ الغربية، والبحث بحاجة إلى مزيد من الجهد نظرا لطول الفترة المدروسة، وبحاجة كذلك إلى إعادة قراءة ما كتبه المؤرخون للخروج من المقاربات التاريخية المتباينة. التي تركها هؤلاء خاصة ما تعلق منها بملامح السلطة والمجتمع. والاعتماد على الكتابات الغربية يفقد البحث الموضوعية لاختلاف اللغة والدين وحالة الحرب غير المعلنة بين المسلمين في المغرب الأوسط وأوروبا، كما هيأت للأفكار المسبقة الخاطئة، التي تبناها أغلب المؤرخين الغربيين. وسوف نحاول تسطير مختلف الخطوط التي ترسم الواقع السياسي في إيالة الجزائر وفعاليات المجتمع الجزائري بمختلف مكوناته، من خلال كتابات بعض المؤرخين الغربيين الذين كتبوا في الموضوع ونقف عليها وعلى رؤاهم المتناقضة أحيانا. The research on the history of Algeria during the Ottoman era is of great importance due to its association with the history of Algeria during the occupation period and the character of modern Algeria that French historians tried to obliterate and dissolve within the Western philosophy of history, and the research needs more effort due to the length of the studied period, and it also needs to re-read Written by historians out of disparate historical approaches. Which they left, especially those related to the features of power and society. Relying on Western writings loses the research's objectivity due to the difference in language, religion, and the state of undeclared war between Muslims in the Middle Maghreb and Europe, as it prepared for the erroneous prejudices adopted by most Western historians.We will try to underline the various lines that draw the political reality in the Eyelet of Algeria and the activities of Algerian society with its various components, through the writings of some Western historians who wrote on the subject and we stand on them and their sometimes contradictory visions
Keywords: المؤرخون الفرنسيون; إيالة الجزائر; العهد العثماني; اللغة والدين; المجتمع الجزائري; French historians; the Eyalet of Algeria; the Ottoman era; language and religion; Algerian society